Tinjauan Yuridis Terhadap Eksekusi Putusan Mahkamah Agung di Bidang Perselisihan Hubungan Industrial - Athari Farhani; I Gede Sandy Satria; Moudy Raul Ghozali (ADALAH, 2022)
Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes has a weakness due to the absence of regulations regarding the execution mechanism after a court decision which has permanent legal force. This has resulted in many executions of PHI decisions that are not carried out properly due to the lack of good faith from the losing party in this case the company to implement the judge's decision. Of course, the most disadvantaged are the workers, because in the case of PHI in the form of Termination of Employment/PHK, workers should receive compensation in the form of wages and severance pay that must be paid by the entrepreneur. This writing uses a normative research method using a case approach and a statutory approach.